2009
DOI: 10.1007/s00415-009-5300-6
|View full text |Cite
|
Sign up to set email alerts
|

Taste in mild cognitive impairment and Alzheimer’s disease

Abstract: In this prospective study we investigated the quantitative and qualitative taste function of patients with mild cognitive impairment (MCI) and Alzheimer's disease (AD). 29 healthy, elderly subjects, 29 MCI and 30 AD patients were tested using a validated taste test, the "taste strips". Additionally, odor identification, odor discrimination, odor threshold, the mini-mental state examination (MMSE) and Apo E epsilon 4 status were examined. Regarding taste, there was a significant reduction of total taste scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
6
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 38 publications
8
82
6
2
Order By: Relevance
“…A more likely possibility is that the general lack of preference for food shown by our participants was related to their clinical condition. Specific food preferences are dependent on sensory capacity (Booth, 1985), which commonly decays in advanced age and is much worsened in individuals with cognitive impairment and dementia (Steinbach et al, 2010). Thus, decreased ability to discriminate taste differences may weaken food preferences, although whether food per se is a less effective reinforcer for patients with dementia cannot be determined from the present data.…”
Section: Resultsmentioning
confidence: 99%
“…A more likely possibility is that the general lack of preference for food shown by our participants was related to their clinical condition. Specific food preferences are dependent on sensory capacity (Booth, 1985), which commonly decays in advanced age and is much worsened in individuals with cognitive impairment and dementia (Steinbach et al, 2010). Thus, decreased ability to discriminate taste differences may weaken food preferences, although whether food per se is a less effective reinforcer for patients with dementia cannot be determined from the present data.…”
Section: Resultsmentioning
confidence: 99%
“…Almost uniformly, participants did not report decline in either olfactory detection or identification, prediction of olfactory identification scores from subjective reports of olfactory function was poor, and awareness of olfactory decline bore no relationship to the likelihood of amnestic MCI patients progressing to Alzheimer's disease by the 12-month review [48]. Another study that looked at both olfactory and gustatory functions found poorer subjective olfactory/gustatory scores in Alzheimer's disease compared to MCI, implicating pathological pattern of hippocampal-parietal memory impairment [50].…”
Section: Awareness Of Olfactory Deficit In Alzheimer's Diseasementioning
confidence: 89%
“…Olfactory impairment has been shown to be predictive of conversion from mild cognitive impairment to AD with a higher than 80% sensitivity (66). With respect to it has also been demonstrated that both cognitively impaired and AD patients present a significant reduction of total taste scores and also individual taste scores on either side of the tongue (67). As sensory modalities are currently further investigated in AD, it appears that these systems may eventually serve as potential “therapeutic gateways” into the psychosocial and physiological alterations in AD (66).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%